A study on the awareness of the Islamic banking system among UMK student - Nurul Aein Khairil Anwar; Nurul Aida Ahmad Nizam; Nurul Aida Lais; Nurul Aisyah Arfiqah Khairul Azmi (2023)
The first Islamic bank is being established in Malaysia after nearly three decades of global knowledge of Islamic finance. The conventional banking industry, which has a longer history than Islamic banking, must compete with Islamic banking. Islamic banks must be cognizant of the elements influencing public awareness, comprehension, and perception of Islamic banking in order to remain competitive. The Islamic financial system is accessible to non-Muslims as well as Muslims. The aim of this study is basically to investigate The Level of Awareness of The Islamic Banking System Among UMK Students' in Kelantan. Influence factors identified and discussed in this study was the knowledge, background, educational status and product quality. Simple random sampling was used in the sample selection. A total of 6806 questionnaires were distributed to UMK students’ respondents in Kelantan, only 364 were returned and can only be used in this analysis. Data in this study were analysed using the "Statistical Package for Social Science" SPSS. Using SPSS tools containing Reliability and Validity Test, Descriptive Testing, Pearson Correlation Analysis and Multiple Linear Regression Analysis, data analysis was carried out. Based on the analytical results of the study, indicate that there is a significant relationship between knowledge, background, educational status and product quality and the level of awareness of the Islamic banking system among University Malaysia Kelantan students. This study is expected to have implications for Islamic banks to attract students UMK towards product and services offered and recommendations for future research related to Islamic banking.